Patterns of Common Diseases in Primary Health Care Settings: A Cross-Sectional Study - Albalawi, Nasser Mohammed; Alatawi, Anor Ali Faraj; GHURM S, ALSHEHRI Dhaifallah; hzazi , Faizah ahmed; Alatawi, Fahad Awad (Journal of Ecohumanism, 2024)
Background: Primary health care (PHC) is the cornerstone of healthcare delivery, addressing the majority of a population’s health needs. Understanding disease patterns in PHC settings is critical for optimizing care, guiding policy, and allocating resources efficiently. This study aimed to identify the most common diseases encountered in PHC and explore their associations with demographic factors. Methods: A cross-sectional study was conducted over three months. A sample of 300 participants aged 18 and above was selected using stratified random sampling. Data were collected through structured interviews and medical record reviews, with diseases classified using ICD-10 codes. Descriptive statistics and chi-square tests were used to analyze disease prevalence and demographic associations. Results: Respiratory diseases (22.5%) were the most prevalent, followed by cardiovascular diseases (18.3%) and endocrine disorders (15.8%). Gender differences were notable, with higher rates of cardiovascular diseases in men (22.2%) and endocrine/musculoskeletal conditions in women (16.7% and 15.2%, respectively). Age-stratified analysis revealed chronic diseases (e.g., cardiovascular, endocrine) were more common in older adults, while younger patients presented more acute conditions (e.g., respiratory, dermatological). Mental health disorders, though less reported (5.8%), were more frequent among women (7.6%). Conclusion: The study highlights the predominance of respiratory, cardiovascular, and endocrine disorders in PHC, with significant variations by age and gender. These findings underscore the need for integrated, demographic-sensitive care models and enhanced PHC services, including mental health and dermatology, to address the evolving disease burden effectively.